2005
DOI: 10.1111/j.1365-294x.2005.02716.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of invasion and colonization of the sea lamprey (Petromyzon marinus) in North America as revealed by microsatellite genotypes

Abstract: Invasions by exotic organisms have had devastating affects on aquatic ecosystems, both ecologically and economically. One striking example of a successful invader that has dramatically affected fish community structure in freshwater lakes of North America is the sea lamprey (Petromyzon marinus). We used eight microsatellite loci and multiple analytical techniques to examine competing hypotheses concerning the origins and colonization history of sea lamprey (n = 741). Analyses were based on replicated invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
172
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(189 citation statements)
references
References 64 publications
15
172
2
Order By: Relevance
“…This corresponds with our findings of no significant differences ( pO0.05) in haplotypic frequencies among collections in other discrete regions, including native landlocked populations in Lake Ontario (three rivers; Waldman et al 2004), in Lake Champlain (four rivers; Waldman et al 2006) and between two rivers in Portugal ( pZ0.8643; Rodríguez-Muñ oz et al 2004). Moreover, it is congruent with findings from nuclear DNA microsatellite analyses for Atlantic coast anadromous sea lamprey populations and among populations in Lakes Ontario and Champlain (Bryan et al 2005). We hypothesize that this panmixia is one outcome of an alternative life-history strategy from that employed by other anadromous fishes, and that this strategy is directly allied with its parasitism.…”
Section: Discussionsupporting
confidence: 77%
“…This corresponds with our findings of no significant differences ( pO0.05) in haplotypic frequencies among collections in other discrete regions, including native landlocked populations in Lake Ontario (three rivers; Waldman et al 2004), in Lake Champlain (four rivers; Waldman et al 2006) and between two rivers in Portugal ( pZ0.8643; Rodríguez-Muñ oz et al 2004). Moreover, it is congruent with findings from nuclear DNA microsatellite analyses for Atlantic coast anadromous sea lamprey populations and among populations in Lakes Ontario and Champlain (Bryan et al 2005). We hypothesize that this panmixia is one outcome of an alternative life-history strategy from that employed by other anadromous fishes, and that this strategy is directly allied with its parasitism.…”
Section: Discussionsupporting
confidence: 77%
“…These findings led Rodriguez-Muñ oz et al (2004) to raise the possibility that the sea-lamprey underwent a severe bottleneck in Southwest Europe. Bryan et al (2005), using microsatellites, also found that in a Portuguese River (Mondego), the genetic diversity was very low when compared with that found in North-western Atlantic rivers, supporting the finding of Rodriguez-Muñoz et al (2004). They suggested that a serious reduction of effective population size may have occurred in Europe as a result of the fisheries that exploit sea-lamprey in several countries.…”
Section: Introductionsupporting
confidence: 75%
“…This lack of differentiation is not caused by insufficient variability in the markers used, as demonstrated by the differentiation among populations of lakes where the sea lamprey is possibly native (Bryan et al, 2005;Waldman et al, 2006). More likely, the lack of structure in Atlantic rivers results from the lack of homing in this species (Bergstedt and Seelye, 1995).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations